Identification of the principles of cleaner production in a red ceramic industry in the municipality of Paudalho-PE - DE MELO, ALCIONE MORAES; COSTA, AMANDA RODRIGUES SANTOS; PAZ, YÊNE MEDEIROS; SANTOS, LILIANA ANDRÉA; EL-DEIR, SORAYA GIOVANETTI; HOLANDA, ROMILDO MORANT (Revista Geama, 2018)
Industrial activities, including red ceramics, cause changes in the environment. The present work had as objective to evaluate the stages of the production process of the red ceramics industry from the Cleaner Production (CP) methodology. For that, a survey of secondary data was carried out, based on bibliographical research in articles, websites and theses related to the theme and primary data, through observational method and interviews. It was observed that the company under study presents some principles of CP regarding the management of production residues, however, there isn’t in fact a planning aimed at executing this tool in its production process. Therefore, it was verified the need for specialized personnel to implement a sustainable management model in the company, to comply with legal specifications, and increase productivity, competitiveness and minimize the consumption of natural resources, being CP a possible tool to be applied for this purpose